The Effect of Different Pt:Ru Surface Composition on Methanol-Oxidation Activity of Carbon-Supported PtRu/IrNi Catalysts. Issue 9 (29th June 2016) - Kaplan, D.; Burstein, L.; Popov, I.; Peled, E.
Abstract : Four PtRu/IrNi/XC72 catalysts, with iridium-nickel core and different atomic ratio platinum-ruthenium shell (Pt25 Ru75 to Pt80 Ru20 ) are synthesized in a two-step deposition process with NaBH4 as the reducing agent. The composition, structure and particle size of the catalysts are determined by Energy–Dispersive X-ray Spectroscopy (EDS), X-ray Photoelectron Spectroscopy (XPS), Scanning Transmission Electron Microscopy (STEM) and Transmission Electron Microscopy (TEM). Electrochemical characterization is performed with the use of cyclic voltammetry (CV). Methanol-oxidation surface and mass activities of the homemade catalysts are studied at 80°C and compared to those of a commercial PtRu alloy catalyst. A correlation between Pt:Ru surface ratio and surface activity is examined. As a result of different platinum utilization of the homemade catalysts, the catalyst with highest surface activity does not show the highest mass activity. Compared to the commercial PtRu catalyst, the mass activity of the best-performing homemade catalyst, in terms of A gPt −1, was higher by 58%, despite the significantly lower surface activity of the latter. The higher mass activity shows the potential of core-shell catalysts for improvement of platinum utilization in anode catalysts for DMFC.